FORECASTING THE URBAN ELECTRICITY SUPPLY SYSTEM - Bo‘riyev Lochin Sobir o‘g‘li; Mirzayev Shoxrux Normurod o‘g‘li; Esonov Temurmalik Beknazar o‘g‘li (PEDAGOGS, 2024)
Forecasting the urban electricity supply system is an important task for energy planning and management. It involves predicting the future electricity demand and supply of a city or a region, taking into account various factors such as weather, economic activity, population growth, consumer behavior, and electricity infrastructure. Accurate forecasting can help optimize the electricity generation, transmission, and distribution processes, as well as reduce the environmental and economic impacts of electricity consumption.